From Assessment to Implementation: Using Qualitative Interviews to Inform Distance Learning Library Services. Issue 1 (2nd January 2017) - Wharton, Lindsey N.
ABSTRACT: While broad assessment projects are often used to steer library strategic planning initiatives, this article will present the benefits of qualitative interviews with distance learning constituents as a framework for developing a focused vision and targeted services. This article will describe the planning and execution of an assessment project used to build a foundation for future library resources and services to target off-campus users. The benefits of this analysis will be detailed. Based on the data, implementation strategies were devised to strengthen and further develop the distance learning unit at Florida State University Libraries.